Bridging Narratives And Neural Rhythms: Qeeg-Guided Storytelling Stimulus With Erodeo For Cognitive Development - Wojtila, Maria Caroline; Juswanto, Gerard Anthonius; Gracia, Anne; Yudha, Rivo Panji (International Journal of Health Sciences, 2025)
Background: Traditional language development interventions for young children often lack personalization and fail to integrate objective neurological data with engaging therapeutic experiences. This study explored children's lived experiences with qEEG-guided storytelling therapy using the innovative Erodeo platform to understand how real-time neural feedback integration with adaptive narratives influences language development processes in early childhood. Methods: A qualitative phenomenological design was employed with 16 children aged 4-8 years who completed qEEG-guided storytelling sessions over a minimum six-week period. Data were collected through child-friendly interviews, parent interviews, and observational sessions, analyzed using adapted phenomenological methods suitable for pediatric populations. Participants were recruited through purposive sampling from pediatric speech therapy centers and early childhood development clinics. Results: Six major themes emerged from the analysis: (1) embodied language awareness - direct felt experience of speech production; (2) immersive narrative engagement - collaborative storytelling enhancing vocabulary acquisition; (3) real-time articulation consciousness - awareness of speech clarity improvements; (4) vocabulary expansion and semantic understanding - enriched word knowledge and usage; (5) communication confidence and social integration - improved expressive abilities; and (6) playful learning empowerment - active participation in language development. Children demonstrated significant improvements in vocabulary acquisition, articulation clarity, and communication confidence. Conclusions: qEEG-guided storytelling therapy facilitates multidimensional language development through personalized, child-centered interventions that honor both objective neurological processes and subjective developmental experiences. This approach offers significant potential for advancing pediatric language intervention by creating dynamic therapeutic environments that adapt to children's developmental needs and learning styles.